Forecasting Performance of Various Volatility Models on Intra-Day Equity Price in the Indian Stock Market - Ahmad, Asad; Rana, U. S. (Indian Journal of Finance, 2012)
In this paper, an attempt has been made to determine the forecasting performance of symmetric and asymmetric volatility forecasting models in terms of error estimators using the intra-day of highly liquid stocks in the Indian stock market. Superiority of forecasting performance of asymmetric GARCH model over symmetric model has been established.